TEXTUAL REASON AND SOCIAL REFORM IN THE 19TH-CENTURY ISLAMIC RENEWAL MOVEMENT - Kholid, Nur; Shobaruddin, Dudin; Al Hanif, Furqon Mahmud; Budiyanto, Sigit (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
The 19th-century Islamic renewal movement emerged as a response to intellectual stagnation and colonial domination in the Muslim world. Reformists like Jamaluddin al-Afghani, Muhammad Abduh, and Rashid Rida advocated for a return to the Qur'an and Sunnah through rational and contextual interpretation—termed